The hungry steppe : famine, violence, and the making of Soviet Kazakhstan - Cameron, Sarah I., 1977- (Cornell University Press, 2018)
"The book brings the largely unknown story of the Kazakh famine of 1930-33 to light, using this case study to overturn several assumptions about violence, modernization, and nation-making under Stalin"--Provided by publisher.